Digitalisation in the German Mittelstand - Popov, Yuri (Tectum Verlag, 2021)
Digitalisation is leading to far-reaching changes and challenges in the German Mittelstand. The Mittelstand refers to the entirety of owner-managed and family-run businesses and contributes significantly to the well-being of the German economy. Although Mittelstand companies are currently highly challenged by digitalisation, they must adapt to new market conditions to ensure competitiveness. Many Mittelstand firms have recognised the need for digital transformation and are now taking action. Thus, this book offers a comprehensive overview of important theoretical perspectives, a detailed analysis of the digital development in the German Mittelstand, and many strategic considerations for a successful digital transformation.With a foreword by Heinz Siebenbrock.